Palindromic and perturbed polynomials: zeros location - Botta, V. [UNESP]; Marques, L. F. [UNESP]; Meneguette Júnior, Messias [UNESP] (Springer, 2014)
We give necessary and sufficient conditions for all zeros of the palindromic polynomial R(z)=1+lambda(z+z (2)+aEuro broken vertical bar+z (n-1))+z (n) , , to be on the unit circle and we find for which S(z)=R(z)+gamma z (n) , n natural, has all its zeros in the closed unit disc.
Keywords: palindromic polynomial; perturbed polynomial; zero